1987
DOI: 10.2307/3577044
|View full text |Cite
|
Sign up to set email alerts
|

16,16-Dimethyl Prostaglandin E 2 Increases Survival in Mice Following Irradiation

Abstract: 16,16-Dimethyl prostaglandin E2 (DiPGE2), a stable analog of PGE2, increases the LD50/30 survival in CD2F1 male mice when given prior to ionizing radiation. Subcutaneous administration of 40 micrograms of DiPGE2 30 min prior to 60Co gamma irradiation extends the LD50/30 from 9.39 Gy in the control animals to 16.14 Gy in DiPGE2 treated, with a dose reduction factor of 1.72 [95% confidence limits: 1.62, 1.82]. The degree of protection is dependent on both the time of administration and the dose of the prostaglan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 11 publications
3
22
0
Order By: Relevance
“…7,8 Recently, CAPE was investigated intensively in a number of animal models and various organs, including kidney, intestine, testis, spinal cord, hindlimb and lung. [7][8]19,20 It has been suggested that CAPE has protective effects against oxidative damage, which has been linked to its free radicalscavenging ability and anti-oxidant capacity. [20][21][22][23][24] Also, CAPE suppresses lipid peroxidation and inhibits lipoxygenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, CAPE was investigated intensively in a number of animal models and various organs, including kidney, intestine, testis, spinal cord, hindlimb and lung. [7][8]19,20 It has been suggested that CAPE has protective effects against oxidative damage, which has been linked to its free radicalscavenging ability and anti-oxidant capacity. [20][21][22][23][24] Also, CAPE suppresses lipid peroxidation and inhibits lipoxygenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous results indicated that spermatogonial stem cells also become less sensitive towards the induction of reciprocal translocations by higher doses of X-irradiation (Sankaranarayanan et al, 1995). So far only prostaglandin-mediated protection responses of in i o cell renewal systems as a whole, such as bone marrow (Hanson & Ainsworth, 1985 ;Walden et al, 1987), hair follicles (Geng et al, 1992), intestine (Hanson & Thomas, 1983) or germinal epithelium, have been described. In the present study we have further dissected this response and show for the first time that the protective effect is clearly present in the stem cell compartment -and, moreover, for both proliferating and quiescent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that various prostaglandins, or synthetic analogues such as misoprostol, protected the mucosa of the digestive tract from injury by non-steroidal anti-inflammatory agents, heat, acids and bases (Robert et al, 1979) or X-irradiation (Hanson & Thomas, 1983). Also other cell renewal systems such as bone marrow (Hanson & Ainsworth, 1985 ;Walden et al, 1987) and hair follicles (Geng et al, 1992) have been found to become more radioresistant by prostaglandin treatment. The mechanism for the radioprotective effect is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Initially it was proposed that the augmentation of radioresponse induced by indomethacin could be due to lowering PGs in tumour tissues. The effects of PGs on radioprotection are, however, not clear: some authors reported that PGs might act as radioprotectors (Hanson & Ainsworth, 1985;Walden et al, 1987), whereas others (Milas et al, 1990) proposed an opposite effect.…”
Section: Radiothinlayer Chromatographymentioning
confidence: 99%
“…Apart from the fact that the mechanisms by which indomethacin potentiates tumour radioresponse are still unclear to date, it appears that an increased tumour response might be achieved by lowering PGs in the tumour. This, however, would imply that PGs are not radioprotective agents as has been suggested by Hanson & Ainsworth (1985) or Walden et al (1987). Milas and coworkers (1990) have also found that potentiation of the tumour radioresponse induced by indomethacin is more significant when it is given after rather than before irradiation.…”
mentioning
confidence: 95%